A criança e a experiência na linguagem poética - Aguirre, Aline (2020)
This dissertation addresses a study on the enunciative experience: the experience of the child's poetic language in verbal interactions produced in the school context. This work is justified by the possibility of establishing a relationship between studies on language acquisition and work with poetic language in Early Childhood Education, through a link between the child's language and the poetic language, which is established from interactions that the child establishes between language and the experience lived with the poetic arrangements made in the speech. This study starts from the main hypothesis that children, in their experience of language, assume poetic arrangements arising from their experiences with poetic language in school contexts. With this hypothesis, the general objective is chosen: To identify, in verbal interactions produced in the school context, how the child experiences the poetic language and how that experience constitutes his experience in language acquisition. The theoretical basis has as main sources the enunciative principles arising from the studies of Benveniste (2006, 2007), the enunciative approach of Silva (2009) and the support of the researches of Diedrich (2015) and Vier (2016), which guide the structuring and establishment of the relationship between enunciation and poetic language. Methodologically, an applied work is proposed, configuring what is meant by an action research, since, based on theoretical and methodological foundations from studies in an enunciative perspective, a work with children is developed, which involves the production of data, the recording and analysis of that data, collected from activities with poetic arrangements, that is, having experiences together and acting actively on a reality in order to transform it. The research project was developed with 12 children from a preschool class, aged between 5 and 6 years old, students at the Casa da Criança Dona Dele Municipal School of Child Education, in Camargo, Rio Grande do Sul State, Brazil. The data recording was performed in audio-visual format, based on four actions developed with the children, in the class in which we are the conducting teacher. The data collected during the action, presented through enunciative clippings, are analysed based on the manifestation of the poetic arrangements that are present in the realization of the discourse. The data obtained in this study indicate that children, from the experience with poetic language, can produce and reproduce poetic arrangements in his daily discourse, inserting themes arising from the experience with the poetics in the verbal interactions they experience with each other. Such arrangements, in the experience of language acquisition, allow the child to experience new relationships with language, play with words, express emotions and feelings, mobilizing poetic art to give meaning to life, presenting innovative combinations of words arising from the relationship that each child mobilizes in the language-discourse from the experience of the poetic function of language.